2020
DOI: 10.1017/ehs.2020.57
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and enculturation in child communication: a cross-sectional study

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…This may lead younger children to create idiosyncratic signs that are difficult to interpret. Supporting this, Lister, Walker, and Fay (2020) found that younger children tend to create signs that are more diverse and idiosyncratic than the signs of older children (i.e., are less enculturated). We speculate that, in addition to being able to create more motivated signs, older children's greater communication success may have resulted from a combination of their greater concept knowledge, their greater enculturation (increasing shared knowledge and the overlap in signs they find salient, relative to other members of their society), and their greater ability to infer others' mental states and use this to inform sign creation.…”
Section: Successful Communication: Motivated Signs Are Just the Beginningmentioning
confidence: 80%
“…This may lead younger children to create idiosyncratic signs that are difficult to interpret. Supporting this, Lister, Walker, and Fay (2020) found that younger children tend to create signs that are more diverse and idiosyncratic than the signs of older children (i.e., are less enculturated). We speculate that, in addition to being able to create more motivated signs, older children's greater communication success may have resulted from a combination of their greater concept knowledge, their greater enculturation (increasing shared knowledge and the overlap in signs they find salient, relative to other members of their society), and their greater ability to infer others' mental states and use this to inform sign creation.…”
Section: Successful Communication: Motivated Signs Are Just the Beginningmentioning
confidence: 80%
“…[39]; for a review, see [134]; but see [135]). These findings have since been replicated in children [136,137].…”
Section: Pantomimic Fossilsmentioning
confidence: 82%
“…The fact that signal universality was positively associated with communication success contributed to the greater success of gesture, compared to vocalization. Consistent with this finding, (hearing and non-signing) adults’ success in interpreting sign language is predicted by the degree to which their gestures resemble the signs from sign language [66] (see also [67]), and children's success in using gesture to communicate is predicted by the degree to which their gestures resemble the gestures of others [50].…”
Section: Discussionmentioning
confidence: 79%
“…However, a recent study indicates that the greater universality of gestured signals (i.e. the degree to which different people produce similar signals to convey the same meaning) may also contribute to their communication success [50]. In this study, children's communication success was positively correlated with the extent to which their spontaneous signals (gesture or vocal) resembled the signals produced by adults for the same meaning, and because signal universality was higher for gestured signals than for vocal signals communication success was higher in the gesture modality.…”
Section: Introductionmentioning
confidence: 99%